(untitled) (Praxis Educativa, 2017)
This research explains in detail the study of experienced teachers of istory, Health Sciences and Technological Sciences, and the development of teaching knowledge regarding pedagogy, the basic profession, and research. The research was conducted from a qualitative paradigm through case studies. This presentation aims at exposing the nuances present in experienced university teaching. To do so, we analyzed the different roles and functions fulfilled by a university professor. We also took into account the many academic and professional traditions that influence the configuration of teachingknowledge. The presence of informal interpersonal relationships was identified as the main source of knowledge. In this sense, there is a need to strengthen guidance and counseling practices performed by more experienced teachers addressed to more novice ones.